Primates in Paradise: Critical Possibilities of the Milieu Movie - David, Joel (Archīum Ateneo, 2024)
The use of multiple lead characters in cinema is a fairly recent development, although the strategy (and its resultant variety of structures) had been present for some time in theater and literature. The typical Classical Hollywood action-driven narrative operated most efficiently through a singular hero, allowing the audience to undergo the film experience via the process of singular identification. With the breakdown in identificatory requisites popularized by various New Wave and Third Cinema movements, and the consequent assimilation of this trend starting with the New American Cinema, mainstream Hollywood was ready to embark upon a series of multi-character movies, with Robert Altman’s Nashville (1975) serving as watershed text. Interestingly, the production of films with multiple lead characters had been a long-standing staple in the national cinema of the Philippines—a country that itself holds multiple distinctions vis-à-vis the US, starting with its historical status as America’s first (and only Asian) colony. This article will be looking at how a mode of practice that recently emerged on the global scene had been functioning in a relatively obscure national cinema, and how the practice ensured for itself a measure of longevity by distinguishing itself as a popular genre.